PENGKAJIAN PENGEMBANGAN BAHASA ANAK DENGAN PENDEKATAN TEORI VYGOTSKY DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA ARAB - Dian Masrura; Agung Setiyawan; Khairuddin Bangun (Raudhah - Proud To Be Professional, 2024)
This research explores the influence of factors such as child innateness and the environment on speech delays, as well as digging deeper into the role of Vygotsky's theory in learning Arabic in Islamic schools. The library research method was used, by collecting data from various literature sources. The analysis was carried out descriptively and objectively. The research results highlight the complexity of children's language development, with an emphasis on environmental influences and the important role of maternal education. Delays in speaking in children are a serious issue that requires attention and support from parents, as well as the importance of implementing a collaborative approach in learning Arabic to facilitate social interaction and a supportive environment.